Hibridno sodelovanje zainteresirane javnosti v procesu obnove območnih gozdnogospodarskih in lovskoupravljavskih načrtov za obdobje 2021-2030 - Poljanec, Aleš (Gozdarski vestnik, 2022)
In the years 2020, 2021 and 2022, the regional forest management and game management plans (hereafter referred to as regional plans) are being revised; they will guide the development of Slovenian forests until 2030. Due to increasing challenges in managing forest ecosystems and the need for harmonization of various interests, participation of stakeholders in the process of preparation of regional plans is of outmost importance. In the current revision of regional plans, a great deal of emphasis was given to the inclusion of forest owners and other stakeholders in the process of preparation of the plans. Formally defined participation was upgraded with more active involvement of the interested public through various presentations, workshops, surveys and meetings. In 2020 and 2021, in addition to the collection of initiatives and public debate and public presentation of plans, 73 workshops on regional and national level with 2000 participants were additionally organized as part of preparation of regional plans. Due to preventive measures due to covid-19, most of the participatory activities in 2020 and 2021 were carried out online, which accelerated the digitalization of forestry. Various tools for digital participation have been developed, from new software solutions on the website to the wide implementation and the use of tools for digital participation. The results of participatory activities were integrated in the drafts of regional plans. The upgrade of participatory approach and the inclusion of the interested public in an early phase of plan preparation contributed to greater coordination of forest management and game management part of the regional plans, to the greater quality and feasibility of the plans and to the harmonization of economic, ecological and social aspects of managing forest ecosystems.
Keywords: gozdno gospodarstvo; gozdnogospodarski načrti; participativno načrtovanje